O Plano Territorial de Qualificação Profissional do Rio Grande do Sul: 2007 em perspectiva - Liedke, Elida Rubini (Revista Segurança Urbana e Juventude, 2010)
The present essay displays the actions of professional qualification offered in Rio Grande Do Sul, in the scope of the national politics of qualification of the Lula government (PNQ) and FHC government (Planfor). It brings social economic characteristics of benefited groups that, according to the guidelines of both plans, must be from workers in a vulnerable position in the business market. Difficulties faced by pupils and professors are considered, against the pedagogical proposals of the plain, to center and contrast the taylorism system, creating a self-employed worker. In the end, questions concerning social and cultural barriers as well as politics against the accomplishment of the pedagogical objectives are discussed, in a context of uncertainties from the global business market.